Optical Properties of Gold After Intense Short-Pulse Excitations - Ndione, P. D.; Gericke, D. O.; Rethfeld, B. (Frontiers in Physics, 2022)
Intense ultrashort laser pulses can create highly excited matter with extraordinary properties. Experimental and theoretical investigations of these extreme conditions are very complex and usually intertwined. Here, we report on a theoretical approach for the electron scattering rates and the optical quantities in gold at elevated temperatures. Our theory is based on the degree of occupancy of the conduction band as well as inputs from ab initio simulations and experimental data. After the electron system has reached a quasi-equilibrium, the occupancy is fully determined by the electron temperature. Thus, our approach covers the important relaxation stage after fast excitations when the two-temperature model can be applied. Being based on the electronic structure of solids, the model is valid for lattice temperatures up to melting but the electron temperature might exceed this limit by far. Our results agree well with recent experimental data for both the collision frequencies and the conductivity of highly excited gold. Scattering of sp- electrons by d-electrons is found to be the dominant damping mechanism at elevated electron temperatures and depends strongly on the number of conduction electrons, hence, revealing the microscopic origin of the conductivity change after heating. The supportive benchmarks with experiments are very valuable as the underlying scattering rates determine a number of other transport, optical and relaxation properties of laser-excited matter.